Sleeplessness Assessing Sleep Need in Society Today - Horne, Jim.; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint: Palgrave Macmillan), 2016)
This book critically evaluates the popular notion that today's society is suffering from 'sleep debt', or what Horne calls 'societal insomnia' - an apparent chronic loss of sleep, which can lead to obesity and related physical and mental disorders including heart disease. It presents evidence which suggests that sleep debt has not in fact worsened to any marked extent over the last hundred or so years, by looking back at some historical writings on sleeplessness and integrating the findings with, evidence-based research that he has undertaken over the last decade. Written in a concise and understandable way, and interwoven with real-world insights, the book will be useful to academic and students of cognitive, critical and social psychology, neuroscience and sociology, as well as anyone who is interested in the social and psychological implications of sleep and sleeplessness. Jim Horne is Emeritus Professor of Psychophysiology at Loughborough University, UK and is a sleep neuroscientist who set up and now runs the Loughborough Sleep Research Centre. He is also affiliated to the School of Psychology, at Leicester University's College of Medicine, Biological Sciences and Psychology, UK, where he works on various cross-disciplinary neuroscience initiatives.
Chapter 1. Insomnia -- Chapter 2. Sleep Debt: Societal Insomnia? -- Chapter 3. Short Sleep, Mortality and Illness -- Chapter 4. Obesity -- Chapter 5. Childhood and Adolescence -- Chapter 6. When is Enough, Enough? -- Chapter 7. Illumination -- Chapter 8. Sleepiness -- Chapter 9. Extreme Sleepiness -- Chapter 10. Brainwork -- Chapter 11. Prolonger Wakefulness -- Chapter 12. Use it or Lose it -- Chapter 13. REM Sleep: 'Food for Thought'? -- Chapter 14. Conclusion.
Keywords: Consciousness; Critical psychology; Applied psychology; Physical anthropology